A novel aqueous two phase system composed of surfactant and xylitol for purification of lipase from pumpkin (Cucurbita moschata) seed and recycling phase components - Amid, Mehrnoush; Hussin, Muhaini; Abd. Manap, Mohd. Yazid; Mustafa, Shuhaimi (MDPI, 2015)
Lipase is one of the important enzymes used in various industries such as food, detergent, pharmaceutical, textile, pulp and paper. A novel aqueous two-phase system composed of surfactant and xylitol was employed for the first time to purify lipase from Cucurbita moschata. The influence of different parameters such as type and concentration of surfactants, concentrations and composition of surfactant/xylitol on partitioning behavior and recovery of lipase was investigated. Moreover, the effect of pH of system and crude load on purification fold and yield of purified lipase were studied. The results of the experiment indicated that the lipase was partitioned into surfactant top rich phase with impurities being partitioned into xylitol bottom rich phase in the novel method of aqueous two phase system composed of 24% (w/w) Triton X-100 and 20% (w/w) xylitol, at 56.2 % of tile line length, crude load of 25% (w/w) at pH 8.0. Recovery and recycling of components also was measured in each successive step of aqueous two phase system. The enzyme was successfully recovered by the method with a high purification factor of 16.4 and yield of 97.4% while phase components were also recovered and recycled above 97%. This study demonstrated that the novel method of aqueous two phase system can be used as an efficient and economical aqueous two phase system rather than the traditional method of aqueous two phase system for the purification and recovery of the valuable enzyme.